Вибір температури заморожування рослинної сировини по вимороженій воді - Ялпачик, Володимир Федорович; Ялпачик, Владимир Федорович; Yalpachyk, Volodymyr; Тарасенко, Віра Григорівна; Тарасенко, Вера Григорьевна; Tarasenko, Vira (My University, 2008)
UK: Робота направлена на дослідження фазового перетворення води в лід деяких видів плодоовочевої' продукції. В результаті проведених досліджень встановлена температура, до якої необхідно проводити процес заморожування. EN: The work is directed on research ofphase transformation of water in frost of some types of products fruit and vegetable. The as a result conducted researches a temperature at which it is needed to produce the process of freezing are resulted in this article.
Keywords: перетворення води в лід; енергія зв'язку; плодоовочева продукція; температура; незамерзаюча вода; заморожування; transformation of water in frost; energy of communication; products fruit and vegetable; temperature; non-freezing water; freezing